Reversible photo-responsive gel–sol transitions of robust organogels based on an azobenzene-containing main-chain liquid crystalline polymer. Issue 7 (22nd January 2020) - Wang, Jing; Jiang, Qian; Hao, Xingtian; Yan, Hongchao; Peng, Haiyan; Xiong, Bijin; Liao, Yonggui; Xie, Xiaolin
Abstract : A robust and photo-responsive organogel has been constructed by introducing an azobenzene-containing main-chain liquid crystalline polymer gelator. Abstract : Stimuli-responsive supramolecular gels have been widely investigated, but the construction of a liquid crystalline gel with a high mechanical property and reversible photo-response still remains a challenge. This is due to the difficulty of designing gelators with liquid crystal properties and gelation abilities in organic solvents simultaneously. In this study, an azobenzene-containing main-chain polyester (Azo-mLCP) with a pendant amide group was synthesized. The organogel of Azo-mLCP via a hydrogen bond in dioxane possessed reversible thermal- and photo-responsive behaviours. The organogel exhibited a good self-supporting ability when the concentration of the gelator was more than 7.5 wt%. The rapid trans -to- cis isomerization of Azo-mLCP in solution was studied via UV-Vis absorption spectra. In addition, the gel-to-sol transition of the organogel could be triggered efficiently by an incomplete trans -to- cis conversion strategy. This study opens a way for the main-chain liquid crystalline polymers to serve in potential applications in photo-responsive robust actuators, electro-optical devices, and so on.